PROBLEMS OF GEOECOLOGICAL IMPACTS OF INADMISSIBILITY OF GROUNDWATER WITHDRAWAL: (on the sample of groundwater withdrawal in RA) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
In the article some implications of technological processes on the change of basic components of the environment are considered that are observed in some of well intakes in Republic. The need to reassess (specify) the exploitation resources of well intakes of Armenia is established. The hydrodynamic method in combination with mathematical modelling is suggested for implementation and revaluation of hydrogeological account of borehole water withdrawal.
Keywords: exploitation resources; groundwater withdrawal; groundwater level; hydrogeological calculations